Magnetoresistance characterization of nanocomposite Fe3O4 / PPy that synthesized with sol-gel spin coating method - Surya Pertiwi; - Ramli (Department of Physics – Universitas Negeri Padang UNP, 2020)
Indonesia is a rich country that has various natural resources, one of which is in the form of mining materials such as iron sand which contains a lot of magnetite (Fe3O4). Magnetite (Fe3O4) has superior properties compared to others so that magnetite (Fe3O4) is a top priority in research activities that are rapidly developing in world research. Polypyrrole (PPy) is a conductive polymer which has several advantages. Fe3O4 nanoparticles are a type of magnetic material that has considerable potential in GMR magnetic sensor applications. The aim of this research is to synthesize and characterize the effect of Fe3O4 composition on the magnetoresistance properties of Fe3O4/PPy nanocomposites synthesized by the Sol Gel spin coating method. In this study, several stages were carried out, namely: the sample preparation stage, the nanocomposite manufacturing stage, the characterization stage and the data analysis. Fe3O4/PPy thin layer nanocomposite is made from iron sand that has been purified and milled by previous researchers. Fe3O4/PPy nanocomposites were prepared using the sol-gel method with a variation of Fe3O4/PPy concentrations of 30%, 40%, 50%, 60% and 70% and then grown using the spin coating method with a rotating speed of 3000 rpm for 60 seconds, the thin layer formed was dried using a furnace at 5500C for 1 hour. Then the thin layer was characterized using XRF, FTIR, SEM and FPP. Based on all the characterizations that have been obtained, a thin layer of nanocomposite has been successfully grown on glass preparations. Fe3O4/PPy nanocomposite thin layer is a thin layer that has good magnetoresistance properties, this is shown in the results of testing the magnetoresistance properties using the Four Point Probe (FPP) method.